Characteristics of youth who leave the emergency department without being seen following sports-related concussion - Jacquelyn J Deichman; Janessa M Graves; Tracy A Klein; Jessica L Mackelprang (Concussion)
Aim: Despite the rising incidence of emergency department (ED) visits for sports-related concussion, the frequency and characteristics of youth leaving before being seen are unknown. Methodology: National estimates of ED visits for sports-related head injuries among youth (10–18 years) were generated for 2006–2017 using the National Electronic Injury Surveillance System. Logistic regression models estimated the odds of leaving without being seen across patient characteristics and time. Results: From 2006 to 2017, 985,966 (95% CI: 787,296–1,184,637) ED visits were identified for sports-related concussions, of which 5015 (95% CI: 3024–7006) left without being seen. Conclusion: Youth with sports-related concussion must receive timely care and ED improvements may reduce rates of leaving without being seen.